1994
DOI: 10.1016/0016-7037(94)90517-7
|View full text |Cite
|
Sign up to set email alerts
|

Isotope and chemical microsampling: Constraints on the history of an S-type rhyolite, San Vincenzo, Tuscany, Italy

Abstract: Fine scale heterogeneities in strontium isotope ratios, 40Ar-39Ar ages, and chemical com~sition have been determined for individual mineral grains and enclaves in the rhyolites of San Vincenzo, Italy. The rhyolites are peraluminous with phenocrysts of alkali feldspar, piagioclase, biotite, and cordierite and have previously been divided into two groups on the basis of whole rock major element chemistry. Group B lavas are distinguished from Group A in having higher MgO and CaO contents as well as containing two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The Tuscan Unit tectonically overlies metamorphic rocks of the Monticiano -Roccastrada Unit (Middle Tuscan Ridge) and is tectonically overlain by the Ligurid Unit. The post-orogenic phase is characterized by extensive magmatism of Pliocene age, and in particular by the 4.4 Ma San Vincenzo rhyolite (Feldstein et al, 1994). Moderately negative inclinations, southerly declinations, high unblocking temperatures, and failure of the fold test also characterize the dominant component of magnetization of the Tuscan Cherts at Monti d'Oltreserchio and Campiglia in southern Tuscany (Fig.…”
Section: Paleomagnetism (This Study)mentioning
confidence: 99%
“…The Tuscan Unit tectonically overlies metamorphic rocks of the Monticiano -Roccastrada Unit (Middle Tuscan Ridge) and is tectonically overlain by the Ligurid Unit. The post-orogenic phase is characterized by extensive magmatism of Pliocene age, and in particular by the 4.4 Ma San Vincenzo rhyolite (Feldstein et al, 1994). Moderately negative inclinations, southerly declinations, high unblocking temperatures, and failure of the fold test also characterize the dominant component of magnetization of the Tuscan Cherts at Monti d'Oltreserchio and Campiglia in southern Tuscany (Fig.…”
Section: Paleomagnetism (This Study)mentioning
confidence: 99%
“…The plagioclase in our sample occasionally has a glass margin of melting probably due to mixing with basic magma (Feldstein et al, 1994). We did not separate this glass margin from the non-al tered phenocryst.…”
Section: Resultsmentioning
confidence: 68%
“…In contrast, Holm and Munksgaard (1982) argued that such 180 enrich ment was caused by metasomatism, and they noted that the phenocrysts in the rhyolites were in iso topic equilibrium. Feldstein et al (1994) found Sr isotope disequilibrium in phenocrysts of plagio clase, feldspar, and biotite in the rhyolite of San Vincenzo. They attributed the grain-size Sr isotope disequilibrium to the systematic isotope heteroge neity in the magma chamber during crystallization.…”
Section: Samplementioning
confidence: 93%
See 2 more Smart Citations